Los jacobinos negros de C. L. R. James: el debate raza/clase en las ciencias sociales caribeñas (2015)
ABSTRACT: This paper analyzes the way in which the Caribbean historian C. L. R. James articulated “race” and “class” perspectives in his book The Black Jacobins. Toussaint L’Ouverture and the Haitin Revolution, published in 1938. To achieve this, some conceptual details are developed from authors such as Stuart Hall, Antonio Gramsci y Franzt Fanon —among others— that reveal that these two dimensions are not antagonistic, but can converge and complement in a complex and multidimensional analytical matrix like the one built by James. This course is intended to demonstrate the originality and richness of thought of James, who in 1938 appeared to be in tune with many of the discussions that would take place in the late twentieth century and early twenty-first in the Social Sciences